Animal sacrifice in the ancient Greek world - Hitch, Sarah ca. 20./21. Jh.; Rutherford, Ian (Cambridge University Press, 2017)
This volume brings together studies on Greek animal sacrifice by foremost experts in Greek language, literature and material culture. Readers will benefit from the synthesis of new evidence and approaches with a re-evaluation of twentieth-century theories on sacrifice. The chapters range across the whole of antiquity and go beyond the Greek world to consider possible influences in Hittite Anatolia and Egypt, while an introduction to the burgeoning science of osteo-archaeology is provided. The twentieth-century emphasis on sacrifice as part of the Classical Greek polis system is challenged through consideration of various ancient perspectives on sacrifice as distinct from specific political or even Greek contexts. Many previously unexplored topics are covered, particularly the type of animals sacrificed and the spectrum of sacrificial ritual, from libations to lasting memorials of the ritual in art